Bivariate Analysis of Age-Related Macular Degeneration Progression Using Genetic Risk Scores. Issue 1 (1st May 2017) - Ding, Ying; Liu, Yi; Yan, Qi; Fritsche, Lars G; Cook, Richard J; Clemons, Traci; Ratnapriya, Rinki; Klein, Michael L; Abecasis, Gonçalo R; Swaroop, Anand; Chew, Emily Y; Weeks, Daniel E; et al.
Abstract: Ding et al. used data from large clinical trials to evaluate the effects of known age-related macular generation (AMD) risk variants on disease progression... Age-related macular degeneration (AMD) is a leading cause of blindness in the developed world. While many AMD susceptibility variants have been identified, their influence on AMD progression has not been elucidated. Using data from two large clinical trials, Age-Related Eye Disease Study (AREDS) and AREDS2, we evaluated the effects of 34 known risk variants on disease progression. In doing so, we calculated the eye-level time-to-late AMD and modeled them using a bivariate survival analysis approach, appropriately accounting for between-eye correlation. We then derived a genetic risk score (GRS) based on these 34 risk variants, and analyzed its effect on AMD progression. Finally, we used the AREDS data to fit prediction models of progression based on demographic and environmental factors, eye-level AMD severity scores and the GRS and tested the models using the AREDS2 cohort. We observed that GRS was significantly associated with AMD progression in both cohorts, with a stronger effect in AREDS than in AREDS2 (AREDS: hazard ratio (HR) = 1.34, P = 1.6 × 10 −22 ; AREDS2: HR = 1.11, P = 2.1 × 10 −4 ). For prediction of AMD progression, addition of GRS to the demographic/environmental risk factors considerably improved the prediction performance. However, when the baseline eye-level severity scores were included as the predictors, any other risk factors including the GRS only provided small additional predictive power. Our model for predicting the disease progression risk demonstrated satisfactory performance in both cohorts, and we recommend its use with baseline AMD severity scores plus baseline age, education level, and smoking status, either with or without GRS.